Women as Migrants and Missionaries - Uchem, Rose (Mission studies, 2014)
There are some commonalities in the experiences of women, migrants and missionaries.In many cultures of the world marriage makes women leave home, father, mother,brothers, sisters and land “for the sake of the gospel (of love);” though with less assuranceof the manifold blessings and eternal bliss promised the missionary (Mark 10:29).Again like migrants, women leave their own family home and go and make anotherhome in another land. In a few cases, marriage and migration bring improved socialstatus for some though not for others. However, when things go wrong whether in thefamily or in the community women, like migrants, get the blame and the shame fromthe wider population. While always free in theory to go back to their original homes, inreality just as migrants and missionaries, women are not all that free to move at will.Intricate social, economic and psychological ties bind many and limit their options forescape. Against this background and from a gender perspective, this paper examinesthe missiological significance of women’s experiences in a given Nigerian immigrantChristian community in the United States of America.